Evaluation of Fatty Acid Compositions of Yogurts in Turkey - Caglayan, Okan; Selim Cakmak, Yavuz; Ozmen Guler, Gokalp; Zengin, Gokhan; Aktumsek, Abdurrahman (Asian Journal of Chemistry, 2014)
In this study, fatty acid composition and conjugated linoleic acid content of some yogurts in Turkey were determined. Total 50 yogurt samples belonging to 16 different national yogurt brands were analyzed by using GC. These samples categorized as whole yogurts, light yogurts, probiotic yogurts and fruity yogurts. Generally, palmitic acid (28.840-30.160 %), oleic acid (26.003-27.533 %) and stearic acid (11.413-12.077 %) were major fatty acids. Total conjugated linoleic acid percentages varied between 0.790 and 0.862 %. The results have shown that fatty acids compositions of yogurts have a desirable characteristic for healthy diet when their levels of conjugated linoleic acid contents are considered.